Student’s Perception towards the Mosque’s Physical Identity in Banda Aceh - Dailami; Maysarah Bakri; Marlisa Rahmi (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
The emergence of various mosque designs today enriches the repertoire of Indonesian architecture. This is due to differences in the understanding of the community and precedents related to Islamic architecture. This phenomenon results in differing perceptions of the physical identity of mosques, including those in Banda Aceh. This research aims to understand the perceptions of UIN Ar-Raniry students regarding the physical identity of mosques in Banda Aceh. Data collection was carried out by distributing questionnaires to 100 respondents. The research results indicate that respondents consider domes as the identity of a mosque.